2013
DOI: 10.1371/journal.pone.0055530
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Megakaryocytic Progenitors from Human Embryonic Stem Cells in a Feeder- and Serum-Free Medium

Abstract: BackgroundThe production of human platelets from embryonic stem cells in a defined culture system is a prerequisite for the generation of platelets for therapeutic use. As an important step towards this goal, we report the differentiation of human embryonic stem cells (hESCs) towards the megakaryocyte (Mk) lineage using a ‘spin embryoid body’ method in serum-free differentiation medium.Methodology and Principal FindingsImmunophenotypic analyses of differentiating hESC identified a subpopulation of cells expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…A recent study demonstrated that the generation of MKs from HPCs is achievable under feeder‐free conditions [18]. However, that study only examined hESCs and used animal‐derived products such as bovine serum albumin (BSA) [18, 21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that the generation of MKs from HPCs is achievable under feeder‐free conditions [18]. However, that study only examined hESCs and used animal‐derived products such as bovine serum albumin (BSA) [18, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The first relies on external signals provided by cytokines or stromal cells to mimic embryonic development and direct sequential differentiation of hPSCs into MKs, a process designated as "directed differentiation" (DD) [227][228][229][230][231]. These protocols are impaired by a lack of efficiency, low purity of the MKs and often rely on serum and xenogenic feeder cells.…”
Section: Mks and Platelets From Human Pluripotent Stem Cellsmentioning
confidence: 99%
“…Recent studies have shown that functional megakaryocytes and platelets can be generated from hESCs and hiPSCs by optimizing culture conditions [40,41,42]. Currently, yields of ~ 60 megakaryocytes per input hESC have been reported [40].…”
Section: Discussionmentioning
confidence: 99%